Valutazione economica di Infliximab (Remicade®) vs Etanercept (Enbrel®) nel trattamento dell’artrite reumatoide - Colombo, G. L.; Muzio, A.; Longhi, A. (Farmeconomia. Health economics and therapeutic pathways, 2003)
Rheumatoid arthritis is one of the most severe chronic pathologies, affecting the whole organism, with invalidating outcomes that affect the quality of life of the patients. Its prevalence is estimated to be about 0,5% in Italy, with elevated costs for the national health system (NHS) and the society, in spite of the best treatment with traditional therapies that include anti-inflammatory and disease modifying antirheumatic drugs (DMARDs). The introduction of new drugs with biological activity, mainly acting through an antagonism of tumor necrosis factor (anti-TNF), is a great advance in the management of the disease, as their use has been shown to be effective in slowing the progression of the joint damage, and sometimes in reversing it,. The present article present a cost-minimization study conducted by comparing the two anti-TNFs available in Italy, etanercept and infliximab, assuming equal efficacy and approached from the perspectives of the Italian NHS and society. Only differential costs were considered, i.e. drug acquisition, drug administration and patient monitoring costs, and the analysis comprised two treatment years, in order two account for the cost differences between the first treatment year and the following. The analysis showed that infliximab represents the more convenient alternative from both the NHS and the society points of view, mainly due to lower drug acquisition costs, which offset the higher drug administration costs: the total two year treatment costs per patient with etanercept resulted of 20.173 euro and 22.164 euro from the societal and NHS perspectives, respectively, while the same costs resulted of 13.715 euro and 14.795 euro with infliximab. These results were tested with thorough sensitive analyses, conducted by varying the principal cost and time consumption estimates, that showed that etanercept results less convenient in all the hypothesis tested.